Improvement in the anti-inflammatory profile with lifelong physical exercise is related to clock genes expression in effector-memory CD4+ T cells in master athletes - de Souza Teixeira, Alexandre Abilio; Minuzzi, Luciele Guerra [UNESP]; Lira, Fabio Santos [UNESP]; Gonçalves, Ana Sofia Vieira Pereira; Martinho, António; Rosa Neto, José Cesar; Teixeira, Ana Maria (My University, 2021)
PURPOSE: Ageing is associated with alterations in the immune system as well as with alterations of the circadian rhythm. Immune cells show rhythmicity in execution of their tasks. Chronic inflammation (inflammaging), which is observed in the elderly, is mitigated by lifelong exercise. The aimed this study was to determine the acute effect of a maximal exercise test on clock genes, regulatory proteins and cytokine expression, and evaluate the effect of lifelong exercise on the expression of clock genes in subpopulations of effector-memory (EM) CD4+ and CD8+T cells and the association of these processes with the inflammatory profile. Therefore, this study aimed to investigate the expression of clock genes in subpopulations of effector memory (EM) CD4+ and CD8+ T cells in master athletes and healthy controls and further associate them with systemic inflammatory responses to acute exercise. METHODS: The study population comprised national and international master athletes (n = 18) involved in three sports (athletics, swimming and judo). The control group (n = 8) comprised untrained healthy volunteers who had not participated in any regular and competitive physical exercise in the past 20 years. Anthropometric measurements and blood samples were taken before (Pre), 10 min after (Post) and 1 h after (1 h Post) a maximal cycle ergometer test for the determination of maximum oxygen consumption (VO2 max). The subpopulations of EM CD4+ and CD8+ T cells were purified using fluorescenceactivated cell sorting. RNA extraction of clock genes (CLOCK, BMAL1, PER1, PER2, CRY1, CRY2, REV-ERBα, REV-ERBβ, RORa, RORb and RORc) in EM CD4+ and EM CD8+ T cells as well as regulatory proteins (IL-4, IFN-γ, Tbx21, PD-1, Ki67, NF-kB, p53 and p21) in EM CD4+ T cells was performed. The serum concentration of cytokines (IL-8, IL-10, IL-12p70 and IL-17A) was measured. RESULTS: The master athletes showed better physiological parameters than the untrained healthy controls (P < 0.05). The levels of cytokines increased in master athletes at Post compared with those at Pre. The IL-8 level was higher at 1 h Post, whereas the IL-10 and IL-12p70 levels returned to baseline. There was no change in IL-17A levels (P < 0.05). The clock genes were modulated differently in CD4+ T cells after an acute session of exercise in a training status-dependent manner. CONCLUSION: The synchronization of clock genes, immune function and ageing presents new dimensions with interesting challenges. Lifelong athletes showed modified expression patterns of clock genes and cytokine production associated with the physical fitness level. Moreover, the acute bout of exercise altered the clock machinery mainly in CD4+ T cells; however, the clock gene expressions induced by acute exercise were different between the master athletes and control group.
Keywords: Ageing; Circadian Rhythm; Cytokines; Exercise immunology; Lymphocytes